Pengaruh Literasi Keuangan dan Gaya Hidup Ibu Rumah Tangga Terhadap Pengelolaan Keuangan Keluarga - Anggraini, Natasya Sabella; Anasrulloh, Muhammad (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research aims to quantitatively describe the influence of financial literacy and housewife lifestyle on family financial management, both partially and simultaneously. The population in this study were all housewives from RW 03 Bayanan, Wajak Lor Village, consisting of 5 RT with a sample of 103 respondents using a saturated sampling technique. Data collection in this research used a questionnaire, with a Likert scale. After that, instrument tests and classical assumption tests were carried out consisting of normality tests, linearity tests, multicollinearity tests and heteroscedasticity tests. The data analysis method uses multiple linear regression analysis, hypothesis testing and coefficient of determination with the help of the SPSS Version 22 for Windows software program. The test results show that Financial Literacy and Lifestyle of Housewives influence Family Financial Management both partially and simultaneously. The results of this research can be used to provide recommendations for Village Government policy making to provide a forum for expanding knowledge about financial literacy to the community.